Simulación mediante ordenador de movimientos bidimensionales en medios resistentes - Martínez-Jiménez, P.; León Álvarez, J.; Pontes Pedrajas, Alfonso (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1994)
We have accomplished a simulation program of mechanics; it is developed in laboratory practice by students in their first years of physics studies at a University level. Its aim is a better understanding of the influence of the variable forces of friction in bidimensional movements. We have verified the effectiveness of this teaching method through the evaluation of the students' progress during the courses in which we have carried out this practice.